2019
DOI: 10.3390/cli7050070
|View full text |Cite
|
Sign up to set email alerts
|

Climate Change-Induced Impacts on Smallholder Farmers in Selected Districts of Sidama, Southern Ethiopia

Abstract: Different factors control the types of adaptive strategies and likelihoods of experiencing climate change-induced impacts by smallholder farmers. By using a mixed research method, this study examines the types and determinants of climate change-induced impacts on smallholder rural farmers in drought-prone low lands of Sidama, Southern Ethiopia. Randomly selected (401) households were surveyed on climate change-induced impacts. Longitudinal climatic data were also collected from the Ethiopian National Meteorolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(35 citation statements)
references
References 39 publications
8
27
0
Order By: Relevance
“…is showed that the areas were vulnerable to the impacts of climate change that influenced the livelihood of farmers directly and indirectly. In line with this result, earlier studies reported that farmers in different parts of Ethiopia faced similar risks with various degrees of severity [60,61].…”
Section: Farmers' Perception Of Climate Change Its Impact and Eir Adaptationsupporting
confidence: 70%
“…is showed that the areas were vulnerable to the impacts of climate change that influenced the livelihood of farmers directly and indirectly. In line with this result, earlier studies reported that farmers in different parts of Ethiopia faced similar risks with various degrees of severity [60,61].…”
Section: Farmers' Perception Of Climate Change Its Impact and Eir Adaptationsupporting
confidence: 70%
“…The multinomial logit (MNL) model was applied to explore factors affecting farmers' perception of temperature and rainfall and the use of adaptation strategies by smallholder maize farmers to reduce the impact of climate change in the study area. MNL is widely employed in climate change adaptation studies [2,32]. The question is how changes in the elements of X effect, keeping other factors constant, and the response probabilities, P(Y = j|x), j = 0.…”
Section: Econometric Analysismentioning
confidence: 99%
“…Climate change affects agriculture and food production through changing agroecological conditions [1]. Sub-Saharan Africa is the most vulnerable region to the impact of climate change and variability due to rainfall-dependent agriculture as well as weak adaptive capacity [2]. Therefore, there is a need to adopt adaptation strategies appropriate for the current and projected climate change [3].…”
Section: Introductionmentioning
confidence: 99%
“…Diseases (Tsetse flies) due to the variability of weather conditions and shortage of feed were seen as major causes of poor animal health. Matewos (2019) reported malaria, cholera, and animal diseases were the most common epidemics attributed to climate change and variability.…”
Section: Conclusion Discussion and Recommendationsmentioning
confidence: 99%